Transfection of exogenous DNA complexed to cationic dendrimer induces alterations of bovine sperm microRNAome - Domingues, William B.; Blodorn, Eduardo B.; Martins, Amanda S.W.; Dellagostin, Eduardo N.; Komninou, Eliza R.; Hurtado, Joaquin I.; Corcini, Carine D.; Varela Junior, Antonio S.; Pinto, Luciano S.; Kremer, Frederico S.; Collares, Tiago; Pinhal, Danillo [UNESP]; et al. (Elsevier, 2020)
MicroRNAs have been hypothesized to be involved in the regulation of male fertility potential. The primary aim of our study was to demonstrate the effects of transfection with dendrimer nanostructure on the parameters of bovine sperm quality and to investigate whether the microRNA profile could be disturbed after cationic dendrimer-mediated exogenous DNA transfection of bovine spermatozoa. The binding of exogenous DNA was significantly increased when dendrimer-based transfection was implemented. However, cationic dendrimer transfection induced detrimental changes in the kinetics and sperm quality parameters, such as membrane integrity, acrosome reaction, and mitochondrial membrane potential, when compared to the control group. Sperm microRNA sequencing revealed 218 known and 106 novel microRNAs in the sperm samples, among which nine were dysregulated after transfection (one was upregulated and eight were downregulated), in comparison to the non-transfected sperm. All the dysregulated microRNAs were related to sperm quality and embryonic development. These results suggest that the transfection process using the dendrimer nanostructure has an impact on the quality and microRNA profile of bovine sperm.
Keywords: Dendrimer; Epigenetic; Gene transfer; Non-coding RNAs; Spermatozoa